Prothrombin Time Sensitivity and Specificity to Mild Clotting Factor Deficiencies of the Extrinsic Pathway: Evaluation of Eight Commercial Thromboplastins - Massignon, D; Moulsma, M; Bondon, P; Debize, G; Abidi, H; Buttin, T; Bon, C; Pillonchery, G; Coeur, P (Thrombosis and Haemostasis, 1996)
Prothrombin-time (PT) sensitivity and specificity to mild clotting factor II, V, VII and X deficiencies have rarely been studied. We therefore carried out a prospective study, in 350 patients, of eight commercial thromboplastins (CTs) in their ability to detect mild clotting factor deficiencies, notably in factor VII. In each patient the factor II, V, VII and X clotting activities and PT performed with each CT were determined. For each CT, PT sensitivity and specificity in detecting factor deficiencies below 0.5 U/ml or below 0.4 U/ml were determined at various PTs, and then Receiver Operator Characteristic curves constructed. At optimum PT threshold level (sensitivity = specificity), exactitude varied from 0.64 to 0.74 (p < 0.01) and from 0.67 to 0.81 (p < 0.0001) in detecting deficiencies below 0.5 and 0.4 U/ml respectively. In conclusion, this study shows the limits of the PT test as performed with 8 CTs in patients with mild clotting factor deficiencies. The impact of such differences in sensitivity and specificity on monitoring certain patients subject to decrease in coagulation factor, and, in particular, of those under low-dose oral anticoagulant, remains to be determined.